2005
DOI: 10.1130/g21475ar.1
|View full text |Cite
|
Sign up to set email alerts
|

Fluid density control on vapor-liquid partitioning of metals in hydrothermal systems

Abstract: Hot aqueous fluids, both vapor and saline liquid, are primary transporting media for metals in hydrothermal-magmatic systems. Despite the growing geological evidence that the vapor phase, formed through boiling of magmatic ore-bearing fluids, can selectively concentrate and transport metals, the physical-chemical mechanisms that control the metal vapor-liquid fractionation remain poorly understood. We performed systematic experiments to investigate the metal vapor-liquid partitioning in model water-salt-gas sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 16 publications
11
118
2
1
Order By: Relevance
“…The Fe/Cl ratio of the liquid remained essentially constant. This is expected from mass balance constraints following the metered addition of a NaCl-Fe-H 2 O source fluid of fixed composition, together with the previously well-established partitioning behavior of Fe that strongly favors the liquid (Bischoff and Rosenbauer, 1987;Pester et al, 2014;Pokrovski et al, 2005). In P-T region 2 (464-466 • C, 29.8-24.7 MPa), halite-vapor coexistence was achieved, which was associated with a sharp increase in the Fe/Cl ratio of the vapor (Fig.…”
Section: Chemistry Of Single Phase Source Fluid and Vapors And Liquidmentioning
confidence: 98%
See 1 more Smart Citation
“…The Fe/Cl ratio of the liquid remained essentially constant. This is expected from mass balance constraints following the metered addition of a NaCl-Fe-H 2 O source fluid of fixed composition, together with the previously well-established partitioning behavior of Fe that strongly favors the liquid (Bischoff and Rosenbauer, 1987;Pester et al, 2014;Pokrovski et al, 2005). In P-T region 2 (464-466 • C, 29.8-24.7 MPa), halite-vapor coexistence was achieved, which was associated with a sharp increase in the Fe/Cl ratio of the vapor (Fig.…”
Section: Chemistry Of Single Phase Source Fluid and Vapors And Liquidmentioning
confidence: 98%
“…Laboratory experiments have demonstrated that charged species, especially divalent transition metals such as Fe, show a strong preference for the liquid phase during vapor-liquid equilibria at elevated temperatures and pressures (Bischoff and Rosenbauer, 1987;Pester et al, 2014;Pokrovski et al, 2005). At the same time, a number of field studies (Beard et al, 2003;Rouxel et al, 2008;Sharma et al, 2001) have considered phase separation as a possible mechanism to induce Fe isotope fractionation in seafloor hydrothermal vent fluids.…”
Section: Introductionmentioning
confidence: 97%
“…Such a fluid derived from the dehydrated oceanic slab is likely to be important in the ore metal enrichment of the adakitic magmas. Because of the highly oxidizing conditions during adakite magma differentiation which destabilize sulfide phases, these metals are easily mobilized likely in the form of chloride complexes by Cl-bearing aqueous fluids (Keppler and Wyllie, 1991;Stolper and Newman, 1994;Keppler, 1996;Frank et al, 2002;Pokrovski et al, 2005) derived from descending, dehydrated oceanic crust. Moreover, the SO 2 ligand which becomes the dominant sulfur species at the expense of H 2 S in the oxidized fluid might also form soluble complexes with chalcophile metals and, thus, further facilitate their mobility.…”
Section: Role Of Slab-derived Fluid In Defining the Geochemistry Of Tmentioning
confidence: 99%
“…The soft chalcophile metals (Au, Cu) form much more stable complexes with soft ligands like HS À than with moderately hard Cl À and OH À /H 2 O in aqueous fluids (e.g., Pokrovski et al, 2005). However, the abundant anhydrite crystallization in melt and fluid (e.g., Pasteris et al, 1996) should result in a decrease of the fluid-phase sulfur contents, causing Cu, Au, Pb and Zn complexation with the far more abundant Cl À in the pre-eruptive fluid, whereas As, Sb and Mo are expected to form soluble hydroxide complexes (e.g., Wood and Samson, 1998;Pokrovski et al, 2005Pokrovski et al, , 2002. High-Al adakitic magmas related to Au/Cu and Cu/Mo mineralization are peraluminous (González-Partida et al, 2003;Reich et al, 2003;Qu et al, 2004;Whalen et al, 2004).…”
Section: Constraints On the Chemistry Of Aqueous Fluidsmentioning
confidence: 99%
“…Vapor phase is known to be more acid and enriched in volatile HCl than the dense brine as show experiments on brine-silicate-vapor systems (e.g., Shinohara and Fujimoto, 1994;Frank et al, 1998). Because antimony chloride and hydroxy-chloride species are more volatile than SbðOHÞ 3 (e.g., Pokrovski et al, 2005b), they are expected to preferentially partition into the vapor phase. This is confirmed by the recent vapor-liquid fractionation measurements which show low values for Sb vapor-liquid partition coefficients, largely in favor of the NaClrich liquid at neutral pH (K Sb = [m Sb in vapor]/[m Sb in liquid]; K Sb $ 0.01-0.001 at 350-450°C).…”
mentioning
confidence: 97%